METHODS AND TOOLS OF PARALLEL CONTROLLED HASHING - Luzhetsky, Volodymyr; Baryshev, Yuriy (Scientific Works of Vinnytsia National Technical University, 2015)
The paper analyses the approaches to the development of driven cryptographic primitives. There had been developed the construction of the driven multi-hash constructions. There had been determined the cryptographic primitives for the reduction functions realization. There had been suggested the approaches to the functions’ synthesis and methods of hashing which use these approaches. There had been presented the evaluations of software implementation performance of these methods.